Inhibition of quorum sensing in a computational biofilm simulation - Lees, M. (2013)
Bacteria communicate through small diffusible molecules in a process known as quorum sensing. Quorum-sensing inhibitors are compounds which interfere with this, providing a potential treatment for infections associated with bacterial biofilms. We present an individual-based computational model for a developing biofilm. Cells are aggregated into particles for computational efficiency, but the quorum-sensing mechanism is modelled as a stochastic process on the level of individual cells.